Urban vs. rural pathways to higher education: analyzing post-2020 educational inequity through family backgrounds and resource allocation in Guangdong - Haishan, Liao; Syed Abdullah, Sharifah Intan Sharina (Human Resources Management Academic Research Society (HRMARS), 2024)
This study investigates the factors contributing to educational inequity between urban and rural areas in Guangdong Province, China, focusing on developments and trends post-2020. Understanding these disparities is crucial in the context of rapid urbanization and economic growth, as they have significant implications for social equality and economic development. Utilizing a quantitative research approach, data was collected from 385 high school graduates using a Stratified Random Sampling method. The study examines variables such as family background, economic capital, and access to educational resources to understand their impact on educational inequity. The methodology involved t-test to enabled the identification of significant differences between the urban and rural areas, and multivariate regression analysis to identify the key factors contributing to these disparities. The findings reveal significant differences in family income, education investment, and infrastructure between the two groups across these dimensions. Despite government initiatives to address these disparities, including teacher recruitment programs and financing reforms, educational inequity persists. The multivariate regression analysis, highlights the critical role of economic capital and family background in perpetuating educational inequities and achieving Sustainable Development Goal 4: Quality Education. These results suggest that, while existing policies have made some progress, they are insufficient in bridging the gap. The study underscores the need for more targeted interventions to promote educational equity, aligning with Sustainable Development Goal 4: Quality Education. Further research is proposed to explore how school and family factors influence students' access to higher education in the post-2020 context.